Reconsidering English Tense Models: A Corpus Approach to EFL Teaching - Muammar Chadafi (JEET, Journal of English Education and Technology, 2026)
This study stems from the confusion that occurs in EFL (English as a Foreign Language) students in learning the division and practice of English tenses in the classroom. The study aims to trace the historical and theoretical development of tense system models in English and evaluate their accuracy and relevance in the context of EFL learning. Through library research and corpus-based analysis, this article reviews the commonly taught 12- and 16-tense models, as well as the minimalist two-tense model proposed in formal linguistics. The findings indicate that the 12- and 16-tense models, although popular in the classroom, often mix aspect and modality, leading to conceptual confusion. Thus, the two-tense model is more in line with linguistic theory and actual usage but less pedagogically elaborates. Therefore, this study proposes a new learning model that integrates corpus-based tense frequency with current linguistic theory as a more accurate and applicable framework for EFL teaching.